Pengembangan Buku Ajar Mata Kuliah Renang Bagi Mahasiswa Pendidikan Jasmani Kesehatan dan Rekreasi - Surahman, Fadli; Yeni, Hilda Oktri (Journal Sport Area, 2019)
This research aimed to develop a coursebook for Swimming course for students of Health, Physical education and Recreation Department of Teacher Training and Education Faculty. The research design was research and development (R &D). Design model that was used by the researchers to produce this product adopted Borg and Gall model. This development research produced a coursebook for Swimming course for student of Health, Physical education and Recreation Department of Teacher Training and Education Faculty. Based on data analysis, the result showed that: 1) average core of language used validation was 78.72% from linguistic validators, 2) average score of media validation was 84.26%, 3) result of first trial for limited scope was 87.5%, 4) result of second trial for wide scope was 87.5%.